ANÁLISE DA PAISAGEM RIBEIRINHA E UMA PROPOSTA DE QUALIFICAÇÃO AMBIENTAL NA LAGOA DO BACANGA, SÃO LUÍS – MARANHÃO: PRESERVAÇÃO E VALORIZAÇÃO - SANTIAGO, Denise Rodrigues (2023)
Rivers and their banks are places susceptible to suffering from population growth and the disorderly urbanization process, causing public health problems and flood risks, for example. Thus, this dissertation aims to analyze the riverside landscape of Lagoa do Bacanga, at the interface between the UFMA Nautical Headquarters and the Sítio do Físico, in order to understand environmental changes and their relationships with society and culture, subsidizing development guidelines for a future proposal for environmental requalification. This region has great economic value, since it concentrates a fishing population, and, in addition, it is physically close to the academic community of the Federal University of Maranhão – UFMA. Despite its physical and biological importance and its privileged location, the region lacks direct support, knowledge generated for the local community, as well as leisure areas. The time frame is concentrated between the years 1970 and 2023, marked by a period of urbanization without proper planning in the city. The research methodology was qualitative, based on literature review, field research and analysis using maps. From mapping the different forms of occupation and uses, environmental zoning, flooding, relief, topography and vegetation, it was possible to suggest a conceptual zoning with uses relevant to society and considering its cultures and cultural heritage. The research concludes that there is a need for more effective urban planning and environmental management in this area, with the aim of minimizing environmental problems, as well as recovery, preservation and enhancement measures for Lagoa do Bacanga and its surroundings.